Characterization of Trudinger's inequality - Ozawa T (Journal of Inequalities and Applications, 1997)
A characterization of a sharp form of Trudinger's inequality is established in terms of the Gagliardo-Nirenberg inequality in the limiting case for Sobolev's imbeddings.